GELIAT, DILEMA SATU RUMAH DUA NEGARA DAN TRADISI KEAGAMAAN SEBAGAI KEKUATAN PEMERSATU DI KALANGAN MUSLIM SEBATIK - Abd Kadir Ahmad (Balai Penelitian dan Pengembangan Agama Makassar, 2020)
Improving the quality of life of the people in the border areas is the concern of the government in a united spirit to develop Indonesia from the edge to achieve national integrity and increase community benefit. One of the prerequisites for the benefit of the community is the maintenance of unity, especially Muslims. This study aims to examine and explore religious traditions as cultural and social capital of the Sebatik people to increase unity in society. The study used a qualitative approach with in-depth interviews, observations, and document reviews used to collect data. The research analysis was conducted descriptively and analytically through the mechanism and process of data reduction, data display and data verification. Documents were analyzed using content analysis. Research findings indicate (1) a number of social, economic, and security issues, as a consequence of Sebatik's position as a border area; (2) however, the problems that arose did not shake the unity and integrity of the local community and the border region between the two countries; (3) one of the binding factors of unity is social and cultural capital in the form of religious traditions as the cultural core of the society supported by the dominant culture of the Bugis people.